P681 Higher in vitro mucin degradation, but no increased paracellular permeability by faecal water from Crohn's disease patients. (27th May 2021) - Becker, H; Kameli, N; Rustichelli, A; Britt, H; Stassen, F; Penders, J; Jonkers, D
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory gastro-intestinal condition with a variable disease course. Impaired intestinal integrity and microbial dysbiosis are associated with disease onset and exacerbations. We hypothesized that a perturbed microbial activity in CD patients may contribute to the impaired barrier function. Therefore, this study aimed to examine the impact of faecal bacterial products of active CD patients, CD patients in remission, and healthy controls (HC) on mucin degradation and intestinal epithelial barrier function in vitro . Methods: Six HC and twelve CD patients were included. Faecal samples were obtained within one week prior to endoscopy processed within 6 hours after collection. Disease activity was determined by the short endoscopic score for CD (SES-CD). Faecal water (FW) and bacterial membrane vesicles (MVs) were applied on mucin agar to determine mucin degradation. Further, differentiated Caco-2 cell monolayers were exposed to FW and MVs to assess transepithelial electrical resistance (TEER) and paracellular junction stability using permeation of fluorescein isothiocyanate-labelled dextran of 4 kDa. Relative abundances of faecal bacterial genera were evaluated by 16S rRNA gene amplicon sequencing. Results: FW-induced mucin degradation was higher in CD samples as compared to HC (p<0.01), but was not linked to specific bacterial relative abundances. FW resulted in 78–87% decrease of TEER in three of the remissive (p<0.001) but not the active CD or HC samples. The decrease of TEER was not linked to increased paracellular permeability. MVs did not induce mucin degradation or epithelial barrier disruption. Conclusion: The higher mucin degradation capacity of CD patient-derived FW might indicate contributions of microbial products to CD pathophysiology and warrants further investigation. Moreover, the altered epithelial resistance in some individuals is not due to paracellular alterations.